DIALECT VARIATION AS AN ACCOMMODATION STRATEGY IN CULTURAL INTERACTION: A Descriptive Study of Ethnic Javanese – Sundanese in Jatinangor - Gartika Rahmasari; Elsa Yuniarti; Iis Kurnia Nurhayati; Iris Fatia Maharani (Fakultas Komunikasi, Sastra, dan Bahasa, 2022)
Jatinangor, West Java has many transmigrators especially from other parts of Java Island such as Central and East Java. Although living in the same island, Javanese people are different in terms of language and dialect from the native people of Jatinangor, Sundanese. The latter tends to be obstacles when Javanese transmigrators want to make a contact with Sundanese people. In order to make an effective communication, both parties need to perform an accommodation strategy so that they can reach their goals in communication. The present study aims to analyze the accommodation strategies performed by Javanese transmigrators and Sundanese natives in Jatinangor. The present study uses a descriptive qualitative approach by interviewing three respondents. The results of present study suggest a convergence strategy to accommodate the communication between Javanese and Sundanese people in Jatinangor. In this regard, both parties change their dialect so that they can be understood better.